2001
DOI: 10.1097/00003246-200111000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with triage to intensive care recommendations

Abstract: Recommendations for triage to intensive care are rarely observed, particularly when the unit is full or triage is done over the phone. These recommendations may need to be redesigned to improve their practicability under real-life conditions, with special attention to phone triage and triaging to a full unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
104
6
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(130 citation statements)
references
References 29 publications
9
104
6
11
Order By: Relevance
“…First, it was performed in a single country. Previous studies have shown that haematological patients are often denied ICU admission based on guidelines from learned societies [30][31][32]. However, guidelines are applied in a uniform manner across industrialised countries [33].…”
Section: Discussionmentioning
confidence: 99%
“…First, it was performed in a single country. Previous studies have shown that haematological patients are often denied ICU admission based on guidelines from learned societies [30][31][32]. However, guidelines are applied in a uniform manner across industrialised countries [33].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies reported substantial improvement in quality both in inpatient [1,11,14,18,21,32,50,53,57,60,62,68,78] and outpatient settings [13,29,37,40,42,46]. Numerous studies, including six RCTs [4,7,38,51,63,71], failed to show any positive effects on quality associated with practice guidelines [5,10,20,25,26,36]. Results were mixed in 12 studies, in which practice guidelines improved quality for certain outcomes or patient subgroups but not others [8,23,24,41,43,52,54,55,58,59,73,74].…”
Section: Do Practice Guidelines Improve Quality Of Care?mentioning
confidence: 99%
“…Studies found greater effect with explicit guidelines [6,13,21,23,50,55], defined as ''systematically developed statements to assist practitioner decisions about appropriate health care for specific clinical circumstances'' [27], although practice guidelines improved both processes and outcomes of care, including cost [14,29,53,62], and the results were greater for performance compared with patient outcomes. Clinician involvement in all aspects of guideline development was vital [5,46,53,73]. However, benefits of comprehensive dissemination and implementation need to be further clarified [36].…”
Section: Do Practice Guidelines Improve Quality Of Care?mentioning
confidence: 99%
“…(3)(4)(5) Genel olarak kaynak paylaşımında yararlılık, kötü davranmama, özerklik ve adalet ilkeleriyle uyum içinde YBÜ kaynaklarının tıbbi durumu geri dönüşlü olan ve tamamen iyileşme için kabul edilebilir ümidi bulunan hastalar için ayrılması önerilir. (6) Bununla birlikte ölçütlerin oluşturulması bunların uygulanması için yeterli değildir. Çünkü özellikle YBÜ yatakları gibi kritik kaynakların paylaşımında ölçütlerin nasıl yaşama geçirileceği önem taşır.…”
Section: Introductionunclassified